Metodologi Ushul Fiqh sebagai Landasan Ijtihad dalam Pengembangan Hukum Tata Negara Islam Kontemporer - Muhammad Faruq; M.Raffi Apriadi; I.M. Aiman Ramadhan. S; Kurniati (AL-Ikhtiar : Jurnal Studi Islam, 2026)
The development of the modern constitutional system presents various new issues not explicitly explained in classical Islamic legal sources. This condition demands ijtihad efforts that can address the challenges of the times without ignoring the principles of Islamic law. This study aims to analyze the role of ushul fiqh methodology as a basis for ijtihad in the development of contemporary Islamic constitutional law. The study uses a qualitative approach with library research. Data were obtained from primary sources in the form of literature on ushul fiqh and Islamic constitutional law, as well as secondary sources in the form of books, scientific journals, and relevant research results. Data collection techniques were carried out through documentation, while data analysis used descriptive-analytical methods. The results of the study indicate that ushul fiqh has a very strategic position as a methodological tool in the ijtihad process to formulate constitutional laws that are in accordance with the development of modern society. Various legal istinbath methods, such as qiyas (equity), istihsan (reasoning), maslahah mursalah (reasoning), sadd al-dzari'ah (reasoning based on the principles of justice), and maqashid al-syari'ah (the principles of Islamic law) provide space for mujtahids to develop constitutional concepts responsive to the needs of the times. Through this approach, basic principles of Islamic law, such as justice, welfare, equality, deliberation, protection of human rights, and government accountability, can be implemented in contemporary constitutional systems. Furthermore, the methodology of ushul fiqh (Islamic jurisprudence) allows for the harmonization of normative Islamic values ​​with modern political, social, and legal dynamics without losing the identity and primary objectives of sharia. Abstrak Perkembangan sistem ketatanegaraan modern menghadirkan berbagai persoalan baru yang tidak secara eksplisit dijelaskan dalam sumber-sumber hukum Islam klasik. Kondisi ini menuntut adanya upaya ijtihad yang mampu menjawab tantangan zaman tanpa mengabaikan prinsip-prinsip syariat Islam. Penelitian ini bertujuan untuk menganalisis peran metodologi ushul fiqh sebagai landasan ijtihad dalam pengembangan hukum tata negara Islam kontemporer. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan (library research). Data diperoleh dari sumber primer berupa literatur ushul fiqh dan hukum tata negara Islam, serta sumber sekunder berupa buku, jurnal ilmiah, dan hasil penelitian yang relevan. Teknik pengumpulan data dilakukan melalui dokumentasi, sedangkan analisis data menggunakan metode deskriptif-analitis. Hasil penelitian menunjukkan bahwa ushul fiqh memiliki kedudukan yang sangat strategis sebagai perangkat metodologis dalam proses ijtihad untuk merumuskan hukum-hukum ketatanegaraan yang sesuai dengan perkembangan masyarakat modern. Berbagai metode istinbath hukum seperti qiyas, istihsan, maslahah mursalah, sadd al-dzari’ah, dan maqashid al-syari’ah memberikan ruang bagi para mujtahid untuk mengembangkan konsep-konsep ketatanegaraan yang responsif terhadap kebutuhan zaman. Melalui pendekatan tersebut, prinsip prinsip dasar hukum Islam seperti keadilan, kemaslahatan, persamaan, musyawarah, perlindungan hak asasi manusia, serta akuntabilitas pemerintahan dapat diimplementasikan dalam sistem ketatanegaraan kontemporer. Selain itu, metodologi ushul fiqh memungkinkan terjadinya harmonisasi antara nilai-nilai normatif Islam dengan dinamika politik, sosial, dan hukum modern tanpa kehilangan identitas dan tujuan utama syariat.